Transforming a Traditional School into a Community (Journal of Parents and Teachers, 2018)
In this article, from the experience of a mother, is related the progressive methodological change undertaken in a public school of Elche. Through training and placing the child as the center of learning, families and teachers have managed to make a school of which they are proud, a better school.
Keywords: methodological change; manipulative mathematics; training; meaningful learning; families